Dusty RF discharges with non-uniform distributions of dust particles - Chutov, Yu.I.; Goedheer, W.; Kravchenko, O.Yu.; Levada, G.I.; Lisitchenko, T.E.; Romanenko, R.O.; Smirnov, R.D. (Вопросы атомной науки и техники, 2003)
PIC/MC computer simulations of dusty RF discharges in argon with various profiles of the dust particle density in the interelectrode gap shows a slow influence of the profiles on a dust particle charge in the quasi-neutral region of the discharges. However the profile influence spatial distributions of electrons and ions in the interelectrode gap as well as the dust particle charge in sheaths.